Pulses of Podzolization: The Relative Importance of Spring Snowmelt, Summer Storms, and Fall Rains on Spodosol Development. Issue 1 (13th January 2015) - Schaetzl, Randall J.; Luehmann, Michael D.; Rothstein, David
Abstract : This study was performed in the eastern Upper Peninsula of Michigan, where Spodosols are extremely well developed. We instrumented a Typic Durorthod with zero‐tension lysimeters to capture water leaving the O, E, and B horizons and with sensors to determine volumetric water contents with depth. We also occasionally measured snowpack depths and determined snow water equivalents. These field data were used to validate a hydrologic model that was run for the site using nearby National Weather Service (NWS) data. Good agreement between the modeled output and field data from the site enabled us to apply 1961 to 2013 NWS data from three additional stations along a transect that spans the range of podzolization strength in Michigan as inputs to the model. Soils remain dry throughout the summer and slowly wet up in fall. The more strongly developed soils in the north are slightly wetter in fall, facilitating breakdown of fresh litter and enhancing production of soluble organic materials. Their translocation into the mineral soil is presumably deepest and most pronounced during snowmelt, facilitated by a strong "pulse" of cold snowmelt water. This pulse comprises well over half of the annual flux of water at 100‐cm depth, even though its timespan is short. Snowmelt fluxes are larger and of shorter duration in the north, where podzolization is strongest. By storing precipitation in a thick snowpack, the pedogenic system compresses inputs of water, creating deeper, more concentrated pulses of percolation when soluble organic materials are readily available; this is the essence of podzolization in this region.